When no news is bad news: communication failures and the hidden assumptions that threaten safety - Macrae, C (SAGE Publications, 2017)
Communication failures in healthcare can be catastrophic. Lost test results, delayed diagnoses, missing handover information: all can have serious impacts on the safety of care with tragic consequences for patients. Even seemingly trivial mishaps can result in disaster. For example, a young mother died after two referral letters were inadvertently addressed to number 16, rather than number 1b, on the road where she lived, meaning diagnosis and treatment of cancer was significantly delayed. Her ten-year survival at the initial point of referral was estimated as 92%. In another case, a patient died of a major haemorrhage during surgery after pre-prepared, cross-matched blood had been incorrectly sent back to the blood bank due a single character in the patient’s name being misspelled. These cases, and many others, point to one of the most insidious risks associated with communication in healthcare: many communicative processes are still commonly viewed as rather mundane administrative tasks – instead of safety-critical processes that are essential to safe care.